2007
DOI: 10.1074/jbc.m607277200
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role of Toll-like Receptor 2 in Nerve Injury-induced Spinal Cord Glial Cell Activation and Pain Hypersensitivity

Abstract: The activation of spinal cord glial cells has been implicated in the development of neuropathic pain upon peripheral nerve injury. The molecular mechanisms underlying glial cell activation, however, have not been clearly elucidated. In this study, we found that damaged sensory neurons induce the expression of tumor necrosis factor-␣, interleukin-1␤, interleukin-6, and inducible nitric-oxide synthase genes in spinal cord glial cells, which is implicated in the development of neuropathic pain. Studies using prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
251
3
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(264 citation statements)
references
References 59 publications
8
251
3
2
Order By: Relevance
“…Mice lacking either toll‐like receptor 2, 3 or 4 show impaired microglial activation in the dorsal horn after PNI42, 43, 44.…”
Section: Microglia In the Spinal Cord In Pni And Diabetic Animalsmentioning
confidence: 99%
“…Mice lacking either toll‐like receptor 2, 3 or 4 show impaired microglial activation in the dorsal horn after PNI42, 43, 44.…”
Section: Microglia In the Spinal Cord In Pni And Diabetic Animalsmentioning
confidence: 99%
“…It was once thought that pain was mediated solely by neurons, however it is now becoming clear that glial in the spinal cord contributes to the initiation and maintenance of pathological pain from a variety of sources [78,79]. Spinal cord glia are activated by sensory signals from the periphery, and similar to infection, release proinflammatory cytokines that contribute to pain [78,80].…”
Section: Role Of Tlrs In Chronic Painmentioning
confidence: 99%
“…Since TLR3 binds mRNA released from necrotic cells it has been suggested that this may be the mechanism responsible for the TLR3 role in neuropathic pain [79]. This indicates that blockade of TLR3 in spinal cord glial cells may potentially be beneficial in the treatment of neuropathic pain [83].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, TLR2 and TLR4 are required for nerve injury-induced microglia activation in the spinal cord. Mice lacking TLR2 and TLR4 show attenuated neuropathic pain (Kim et al, 2007;Tanga et al, 2005). However, the cellular localization and injury-induced regulation of TLRs in the spinal cord remain to be investigated.…”
Section: The Role Of Microglia In Pain Controlmentioning
confidence: 99%